Peran Kampus Mengajar Sebagai Usaha Meningkatkan Kemampuan Literasi dan Numerasi di SMP Darussalam NW - H, Hilmiyatun; Aryani, Fedya Diajeng; Inayati, Siti Reuni; Ihsani, Baiq Yuliatin (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The Teaching Campus Program is one of the flagship programs of the Independent Learning Campus (MBKM) policy of the Ministry of Education, Culture, Research and Technology (Kemendikbudristek). The Teaching Campus Program is a program that provides opportunities for students to learn outside the classroom by becoming partners with teachers in the learning process in basic education units. This program focuses on two outcomes, namely developing the competency of students participating in the program through increasing leadership capacity, creativity and innovation, problem solving, communication, team management, and improving analytical thinking, as well as increasing literacy and numeracy for students at target schools. This context is getting stronger considering that Indonesia's literacy and numeracy conditions are still low in line with efforts to increase literacy and numeracy as one of the national priority agendas. The methods used include observation methods, observation methods and interviews. The results of this activity are the impact of improving student learning outcomes at Darussalam NW Middle School and helping technology adaptation for students, teachers and schools in accordance with achieving the objectives of the Teaching Campus Program, namely that students, teachers and schools are expected to be technologically literate. Students who previously could not operate a computer, since the technology adaptation program was implemented, students have been able to perform basic computer operations and use Microsoft Word and Excel. The Angakatan 5 Teaching Campus Program which has been implemented at SMP Darussalam NW has provided a variety of new innovations in learning activities. However, the results of this program will be maximum if teachers continue to want to learn and make efforts and are aware that the role of technology in the learning process is very important.